Strategi Penanaman dan Pelaksanaan Nilai Moral Agama Pada Anak Usia Dini - Rahma, Yudia; Raihana, Raihana (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
The purpose of this research was to find out how the implementation of moral and religious values ​​was instilled in children at the Harapan Bunda Sungai Pagar PAUD Post, Kampar Kiri Hilir District, Kampar Regency. Qualitative research with a descriptive approach is the research method used in this research. This involved two main informants, namely teachers at the PAUD Post and one person as a supporting informant, namely the Principal of the PAUD Post School. Data collected for research uses interviews, observation and documentation. Meanwhile, analyzing this research begins with collecting data, reducing the data, then presenting the analyzed data and finally withdrawing the data for verification. The results of this research show that the instillation of moral and religious values ​​at the Harapan Bunda PAUD Post is carried out by teachers through 1) the storytelling method, this method is used because it is considered effective in instilling religious and moral values ​​in children, children understand more quickly if the instillation of religious moral values ​​is carried out. by telling stories. 2) habituation, this method is carried out every day through examples given by the teacher and this is always done so that children become accustomed to it and 3) conversations between the teacher and students.